Knowledge, attitudes, and practices (KAP) towards COVID-19 among university students in Pakistan: a cross-sectional study - Shah Faisal, - (2191-0286, 2021)
Objectives Pakistan has taken unprecedented measures to control the spread of COVID-19. Complete lockdown followed by smart lockdown and quarantine centres was established. Their awareness and attitude towards COVID-19 had an impact on the individual behaviour of the precautionary measures. The current study examined the knowledge, attitudes and practices of university students in Pakistan.